2020
DOI: 10.3892/ol.2020.12068
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of extranodal marginal zone lymphoma using next generation sequencing

Abstract: Extranodal marginal zone lymphoma is a type of low-grade B-cell lymphoma that can be classified as a mucosal-associated lymphoid tissue (MALT) lymphoma. Recently, second-generation or next-generation sequencing (NGS), which allows simultaneous sequencing of hundreds to billions of DNA strands, has been a focus of attention and is rapidly being adopted in various fields. In the present study, paraffin-embedded tissue samples of gastric MALT lymphoma (n=1) and small intestine MALT lymphoma (n=4) were selected, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…have also previously been identified in primary CNS lymphoma (109), primary gastrointestinal lymphoma (110) and ovarian and other extranodal DLBCL (111). The clinical significance of these mutations is currently unknown, but frequent non-frameshift insertions have previously been documented in NCOR2 in extranodal marginal zone lymphoma which were observed to reduce function (112). In this study, in-frame insertions were observed in 4 samples.…”
Section: Ighv4-34 Hydrophobic Patch Region Is Frequently Preserved In...mentioning
confidence: 49%
“…have also previously been identified in primary CNS lymphoma (109), primary gastrointestinal lymphoma (110) and ovarian and other extranodal DLBCL (111). The clinical significance of these mutations is currently unknown, but frequent non-frameshift insertions have previously been documented in NCOR2 in extranodal marginal zone lymphoma which were observed to reduce function (112). In this study, in-frame insertions were observed in 4 samples.…”
Section: Ighv4-34 Hydrophobic Patch Region Is Frequently Preserved In...mentioning
confidence: 49%